Multidimensional Preinjury Health and 6-month Outcome After Traumatic Brain Injury in Older Adults Presenting With Mainly GCS 13–15 - Roy Tzemah-Shahar; Yael Rosen Lang; Ava M. Puccio; Esther L. Yuh; Domenico Lombardi; Michele Diaz Nelson; John Boscardin; J. Russell Huie; Kristine Yaffe; David O. Okonkwo; Ramon Diaz Arrastia; Geoffrey T. Manley; et al. (Journal of Head Trauma Rehabilitation, 2026)
Objective: To test the accuracy of existing traumatic brain injury (TBI) outcome prediction models in older adults with TBI (oaTBI), to determine the independent association of 5 different measures of preinjury health with 6-month outcome, and to investigate whether these preinjury health measures improve outcome prediction. Setting: Two level 1 trauma centers. Participants: A total of 112 adults aged ≥65 years who underwent head computed tomography after acute TBI (95% with Glasgow Coma Scale (GCS) score 13–15, 66% with acute intracranial trauma on head CT). Design: Prospective cohort study. Main Measures: Preinjury health was characterized using activities of daily living (ADL), Functional Activities Questionnaire (FAQ), Clinical Dementia Rating (CDR), Charlson Comorbidity Index (CCI), and Groningen Frailty Index (GFI). The primary outcome was poor recovery (Glasgow Outcome Scale–Extended